Acylfulvenes covalently interact with thioredoxin as an additional cancer target - Slappendel, Laura; Liu, Xiaodan; Macarthur, Michael R.; Sharpless, Charles M.; Sturla, Shana J. (Frontiers in Chemical Biology, 2024)
Maintaining cellular redox homeostasis is critical for cell viability and growth, with disruptions implicated in cellular responses to chemicals and drugs. This study investigates the interactions between acylfulvenes (AFs), a class of DNA alkylating drugs, and thioredoxin (Trx), a key redox regulating enzyme. AFs are semi-synthetic derivatives of the natural product illudin S. While their cytotoxic properties are widely attributed to DNA alkylation, they also react with cellular thiols, such as Trx, and the implications of these interactions remain poorly understood. Through biochemical assays with isolated E. Coli Trx, and cellular experiments in a human cell line (HeLa), we elucidate AFs' impact on Trx activity and cellular levels. AFs, particularly hydroxymethylacylfulvene (HMAF), inhibited Trx activity by covalently modifying its active site cysteines.Drug exposure also altered cellular Trx levels and nuclear accumulation. In contrast, illudin S, which has a less selective toxicity profile for cancer cells, minimally inhibited isolated Trx. These data underscore Trx as a potential target contributing to the chemotherapeutic potential of AFs and provide insights into molecular interactions governing their impact on cancer cells.